Precolonial Igbo Voices in Akwaeke Emezi’s Freshwater (2018): A Palimpsestic Search for “Home” - Ossana, Eugenia (Complutense Journal of English Studies, 2021)
The present article examines how Freshwater (2018), the debut novel of the Nigerian writer Akwaeke Emezi, offers a layered portrayal of precolonial Igbo and western narratives. By recourse to the auto-fictional narrative mode, the fiction deploys a constant tug of war which suggests the culturally hybrid nature of discourses connected to spiritual belief, self-identity dynamics and gender. My analysis pivots around three main discussions. Firstly, I trace and exemplify the aesthetic and thematic imbrication between Igbo cosmology (and Animism) and Christianity. Secondly, I seek to evince the unconventional depiction of plural consciousnesses coexisting in an individual in an effort to contest long-established truisms of self formation. I also focus on the ensuing amalgam between western conceptions of mental illness, trauma and Igbo mystic interpretations of reality. Considering the peripheral Igbo stance the novel depicts, the fiction will be contextualised within the current literary meta- and trans-modernist axis. Thirdly, I refer to transgender issues mapped up and brought to the fore through the main character’s predicament; a search for existential answers commingling divergent paradigms. Thus, Freshwater offers a peculiar polyphony of numinous narratorial voices which strive to question extant (neo)postcolonial truths.